Teacher Argelia Mercedes Laya López. Contributions to the Afrodescendant venezuelan imaginary (1926 - 1997) - Mora García, Jose Pascual (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This study analyzes the social imaginaries that fostered the Afrodescendant culture in Venezuelan society, the history of mentalities and social imaginaries were the methodological referents, having as source the case of the social activist and teacher Argelia Mercedes Laya López (1926-1997). The teacher Argelia Laya is of African descent and stood out for developing the “mental scaffolding” for the rights of Afrodescendants and mainly for vindicating the rights of women regardless of color or social class. Her status as social activist and her teacher role helped undermine the juxtaposition of sectarian cultures in Venezuela and the development of equal rights in a culture of Afrodescendant venezuelans. To conclude, the study of the social imaginary in Argelia Laya allows us to point out that her main contribution lies in the vindication of Afrodescendants with criteria of class equality, even beyond ethnicity, her struggle is the struggle of all women, without any discrimination.